2015
DOI: 10.1155/2015/615740
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced k-Means Clustering Algorithm for Pattern Discovery in Healthcare Data

Abstract: The huge amounts of data generated by media sensors in health monitoring systems, by medical diagnosis that produce media (audio, video, image, and text) content, and from health service providers are too complex and voluminous to be processed and analyzed by traditional methods. Data mining approaches offer the methodology and technology to transform these heterogeneous data into meaningful information for decision making. This paper studies data mining applications in healthcare. Mainly, we study k-means clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“… Algorithm 3 illustrates the algorithm. In the proposed methodology K -means algorithm starts off with assigning K initial centroids identified in Phase II (which is not the case in general K -means) to K clusters and repeatedly performs the following steps:Compute the Euclidean distance.Assign the data objects in D to their corresponding clusters depending on the Euclidean distance.Recompute/revise the cluster centroids [31]. …”
Section: Proposed Methodologymentioning
confidence: 99%
“… Algorithm 3 illustrates the algorithm. In the proposed methodology K -means algorithm starts off with assigning K initial centroids identified in Phase II (which is not the case in general K -means) to K clusters and repeatedly performs the following steps:Compute the Euclidean distance.Assign the data objects in D to their corresponding clusters depending on the Euclidean distance.Recompute/revise the cluster centroids [31]. …”
Section: Proposed Methodologymentioning
confidence: 99%
“…The authors have tried to improve the k-means algorithm from only algorithmic point of view. K-means can provide patterns which can be very useful for making good decisions 8 . While in this work algorithmic as well as architectural point of view is explored.…”
Section: Algorithmmentioning
confidence: 99%
“…To make sense out of this data, medical practitioners and service providers can apply various data mining algorithm, to discover various patterns and useful insights. Such insights can be very useful on understanding various trends during epidemics, such as Malaria, Dengue, Chikungunya and other such outbreaks [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The study outcome was found to have better performance compared to existing clustering and optimization techniques. Haraty et al [26] have enhanced k-means clustering for extracting diversified patterns from the medical data. The algorithm also uses greedy approach, where the outcomes of the study have been evaluated with respect to a number of items in dataset and fmeasure, a coefficient of variance, etc.…”
Section: Existing Research Workmentioning
confidence: 99%